Legal Protection for Women in Marriage Law in Indonesia - Abdillah, Kudrat (TERAJU: Jurnal Syariah dan Hukum, 2025)
Throughout history, women have been treated as second-class citizens and subjected to endless discrimination, from the time of Ancient Greece, the pre-Islamic Jahiliyyah period, the arrival of Islam, to the present day. Islam has arrived and, normatively, one of its aims is to elevate the status of women, especially in the realm of marriage. In Islamic marriage, women are treated as equals to men in terms of their roles, access, and opinions. In positive law, marriage in Indonesia is very friendly and caring towards women. This paper focuses on how the values of Pancasila are integrated into each article of marriage law. This is because Pancasila is a way of thinking and a way of life for Indonesian society. This paper is a qualitative study and is a type of normative research that examines library literature. The results illustrate how Indonesian marriage law protects women's rights, both physically and psychologically. In this case, there are four things that are examined. (1) The right to choose a partner. Indonesian marriage law stipulates that without the consent of the prospective bride and groom, the marriage cannot take place. This provision gives every citizen the right to have the opportunity to choose to form a family of their choice. (2) Marriage Registration. In this marriage registration, every marriage must be registered as a form of authentic evidence and legal certainty. (3) Marriage age limit. Indonesian marriage law regulates the minimum age limit for prospective brides and grooms, which is nineteen years old. This is regulated because physically and mentally, Indonesian society in general is considered ready for marriage at that age to avoid various adverse effects. (4) Taklik Talak. The taklik talak agreement strengthens women's rights in marriage by guaranteeing them easy access to file for divorce if their rights are not fulfilled by their husbands. From the several aspects discussed, the values of Pancasila that form the spirit of Indonesian marriage law are the values of divinity, humanity, and justice.